Biblical Perspective and Educational Domains in Sex Education: Addressing Gaps in Indonesian Sex Education - Idayanti, Esther; Oentoro, Jimmy Boaz; Silalahi, Frans (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
In Indonesia, sex education is delivered in public high schools as part of the biology curriculum and under the topic of reproductive health. According to the government’s view, when schools teach students properly about reproductive health, they will have a good understanding of their sexuality. Therefore, there is no need to have any further sexual education outside of the school curriculum. However, about half of the teenagers living in major cities are involved in premarital sex, and the rate of teen abortion and HIV infections is high. This article examined the implementation of sexual education in public high schools in Indonesia using a combination of qualitative and quantitative research. The survey was done on a sample of 416 students from 30 provinces and 66 cities in Indonesia. The finding support a particular approach to sex education that incorporates cognitive, affective, and psychomotor learning aspects of educational taxonomy. We find that it is essential to develop a separate sex education module in addition to the current reproductive health topic taught in biology to encourage students to practice abstinence, rather than just teaching reproductive health.